Kinetic of biogas production from oil palm empty fruit bunches (2014)
The production process of oil from Elaeis guineensis palm produces an organic residual. Oil palm empty fruit bunches (OPEFB) are one of the main waste products, representing 7%. Up to now, OPEFB aren't totally used, being an environmental problem. In this paper, the employment of OPEFB pretreated with NaOH is studied as a raw material for biogas production. The pretreatment time (PT) of the OPEFB influences directly on biogas production achieving conversions of volatile solids to biogas of 96% for PT=60 min and 29 days of reaction. Biogas production is adjusted to a first order kinetic law, with kinetic constants for the generation of CH4 (0,108 d-1) and CO2 (0,107 d-1) at the reactor operating temperature (55°C). Finally, a general model is obtained to estimate volatile solids conversion to biogas as a function of pretreatment time and of the residence time inside the reactor.